Effects of fibre loading and nano-silica on physical, mechanical and thermal properties of bagasse fibrefilled recycle high-density polyethylene - Salleh, Qamariah Norhidayah (2019)
Fibre-reinforced composite (FRCs) is an attractive natural fibre-based material to many applications due to its desirable properties including high strength-to-weight and stiffness-to-weight ratios, and corrosion resistance. In recent years, growing interest in FRCs has promoted an increase in engineering application such as aerospace, defence, automotive, construction, marine and oil and gas. As referred above, FRC is made of thermoplastic polymer reinforced with natural fibre to form into board. Natural material in form of fibres or flour is added into polymer matrix such as recycled high-density polyethylene (rHDPE) to form FRC. The composite made from wood and natural fibres are environmentally sound due to its biodegradable properties. Synthetic filler such as nano-SiO2 is often used in FRC to enhance its properties. Since, FRC has a high potential to be alternative material in various industries, the better knowledge on physical, mechanical and thermal properties are the main concern in this study. Hence, the aim of the research was to examine the effect of bagasse fibre loading and nano-SiO2 on the physical and mechanical properties of bagasse/rHDPE composite. This study also investigates on the thermal properties of bagasse/rHDPE composite in response to different fibre loading and nano-SiO2 content via dynamic mechanical analysis. For this purpose, bagasse fibre in 0.5-0.9mm and 1.0- 1.4mm particle size and various weight ratios (30 wt%, 50 wt% and 70 wt%) were mixed with rHDPE. In order to increase the interfacial adhesion between the filler and the matrix, MAPE was used as coupling agent. Nano-SiO2 with weight ratio of 0, 2, 4wt% were utilized to enhance the composite properties. The physical properties (water absorption and thickness swelling) and mechanical properties (tensile, flexural and impact strength) were carried out on the samples based on ASTM standards. To determine the thermal properties of composite, DMA test was carried out. The mechanical properties of BF/rHDPE composite shown an improvement with the addition of 30 wt%, 50 wt% and 70 wt% of fibre content. The study finds that composite with 70 wt% had the highest value of modulus of rupture (MOR), modulus of elasticity (MOE), tensile and impact strength compared to 30 wt% and 50 wt% fibre loadings. Modification of the composite using nano-SiO2 filler has showed that composite with 4 wt% performed significantly better than 0 wt% and 2 wt% in tensile, flexural and impact strength properties. This study also indicates that water absorption (WA) and thickness swelling (TS) of BF/rHDPE composite increases with fibre loadings. Similar trends were observed with BF/rHDPE composite of larger particle size. The result for dynamic mechanical analysis (DMA) has indicated an increase of storage modulus (E’), loss modulus (E”) and loss factor (tan δ) with the incorporation of short fibre (0.5-0.9mm) at 70 wt% fibre loading and 4 wt% of nano-SiO2. Overall, BF/rHDPE composite produced with 70 wt% BF and 4 wt% of nano-SiO2 had the best improvement in terms of physical, mechanical and thermal properties.